Correction: Underestimation of Leptospirosis Incidence in the French West Indies. - Sylvie Cassadou; Jacques Rosine; Claude Flamand; Martina Escher; Martine Ledrans; Pascale Bourhy; Mathieu Picardeau; Philippe Quénel (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0004668.].